"Alles is politek, maar politiek is nie alles nie": Het Kuitert gelyk? - Vorster, Willem S. (Hervormde teologiese studies, 1988)
'Everything is politics but politics is not everything': A critical discussion of Harry Kuitert's viewpoint on faith and politics A critical review is given of Kuitert's position on faith and politics developed in one of his recent publications. After a general survey, the idea of the two regiments to which Christians belong, is discussed. Then attention is paid to the source(s) from which Christians derive principles for political and social decisions. The implications of Kuitert's views are summarised in a next section. In conclusion the question whether Kuitert is correct is discussed with a view to the South African situation.